Biological response and phytoremediation of perennial ryegrass to halogenated flame retardants and Cd in contaminated soils. Issue 6 (December 2021) - Xie, Hui; Ma, Yuhan; Wang, Yuying; Sun, Fengxia; Liu, Ruiyuan; Liu, Xin; Xu, Yuxin
Abstract: Two halogenated flame-retardants and cadmium in soil is harmful to human health, in order to study the biological response and bioaccumulation ability of ryegrass to pollution stress, the phytotoxicity to seedlings and the phytoremediation effect in contaminated soil were investigated. It showed that proline and malonaldehyde (MDA) contents and antioxidant enzyme activity of ryegrass seedlings were increased, cadmium was the most toxic to ryegrass seedlings. The bioconcentration factor (BCF) of roots is higher than shoot. Ryegrass could assimilate trace amount of Dechlorane Plus (DP) and Tetrabromobisphenol A (TBBPA), and its dissipation in soil mainly due to the root exudates and rhizosphere microorganisms. T1/2 of syn-DP, anti-DP and TBBPA was 42.01, 39.38 and 74.53 d in the single pollution, T1/2 prolonged in combined pollution. Cadmium in the roots and stems is 27.82 mg/kg and 10.25 mg/kg in the treatment of single pollution, biological accumulating coefficient (BAC) and biological transfer coefficient (BTC) were 2.16 and 0.37. Ryegrass could effectively reduce total cadmium in soil; the optimal bioremediation time was 60 days. The phytoremediation ability and phytoextraction efficiency of ryegrass in contaminated soil were clarified, which would be useful for understanding the fate of halogenated flame-retardants and Cd in phytoremediation for contaminated soil. Graphical Abstract: ga1 Highlights: The bioaccumulation factor of ryegrass roots to two flame-retardants and Cd in soil is higher than shoot. Ryegrass significantly reduced the half-lives of DP and TBBPA dissipation in soil. Ryegrass could reduce total cadmium in soil, the optimal bioremediation time was 60 days. The phytoremediation ability and phytoextraction efficiency of ryegrass in contaminated soil were clarified.